Diagnostics and treatment of chronic constipation in adults: clinical guidelines of the Russian gastroenterological association - V. T. Ivashkin; I. V. Mayev; A. A. Sheptulin; A. S. Trukhmanov; Ye. A. Poluektova; Ye. K. Baranskaya; O. S. Shifrin; T. L. Lapina; M. F. Osipenko; V. I. Simanenkov; I. B. Khlynov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of publication. To present the modern concept on etiology and pathogenesis of constipation, its classification, basic diagnostic and treatment methods to general practitioners. Summary. The prevalence of constipation in general population is quite high and averages 12 to 19%. Two types of constipation are usually distinguished: primary (functional) and secondary that is related to mechanical obstruction of the intestinal passage of bowel content, neurologic and endocrine diseases, systemic diseases of connective tissue, intake of drugs etc. At diagnosing of functional constipation early detection of «alarm symptoms» which require thorough patient investigation is important. Moreover, insufficient treatment response require step-by-step instrumental diagnostics. Constipation treatment has to be comprehensive and include general recommendations (intensification of physical activity, increase in dietary fiber in daily ration etc.), intake of psyllium, laxatives, including first of all of polyethyleneglycol, at insufficient response enterokinetic agents. Conclusion. Successful treatment of constipation requires correct detection of its cause, following essential dietary recommendations and stepwise application of pharmaceutical agents.